Diabetes Dictating Policy: An Editorial Commemorating World Health Day 2016 - Amirhossein Takian; Sara Kazempour-Ardebili (Kerman University of Medical Sciences, 2016)
The 21st century is an era of great challenge for humankind; we are combating terrorism, climate change, poverty, human rights issues and last but not least non-communicable diseases (NCDs). The burden of the latter has become so large that it is being recognized by world leaders globally as an area that it is in need of much greater attention. In light of this concern, the World Health Organization (WHO) dedicated this year's World Health Day (held on April 7, 2016) to raising international awareness on diabetes, the fastest growing NCD in the world. This editorial is an account of the macro politics in place for fighting diabetes, both internationally and nationally.